STRATEGI KOMUNIKASI BADAN PENANAMAN MODAL DAN PROMOSI DAERAH (BPMPD) PROVINSI RIAU DALAM MENARIK INVESTOR ASING - Novelda Riyanti; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Investmentandpromotion ofan important partineconomic growth in both the local and national scale. Efforts investment activity in the regionis one of support acceleration of economic development. Riau economic growth above the national economic growth of 7.55 percent, it encouraged foreign investment and improving the investment climate in the country in Riau 1304.90 Million US$ in 2013 and Rp 4.8 trillion 2013. In connection with that, investment and promotion agency of the province of Riau has the authority to continue to increase promotion and investment in Riau. This study aims to determine the message communication planning, media planning and communication purposes BPMPD communication strategies in attracting foreign investors.This study uses qualitative research methods with a presentation of the descriptive analysisis to illustrate and describe the state of the subject or the object of research, at the present time based on the facts that appear. This study uses amodel interactive data analysis of Hubermen and Miles, using the technique of checking the validity of the data through the extension of participation and triangulation.The resultsofthis studyshow; first, planning communication message BPMPD of Riau Province is khlayak analysis, create a message with emphasison the basic or messages, organize messages and make callson the style and message. Second, communication media planning BPMPD of Riau Province, selecting media and determine the budget of the media to be used. Third, the purpose of the strategy BPMPD of Riau Province provide information about potential and investment opportunities in the province of Riau to domestic investors and foreign investors through promotional efforts, to foster the implementation of capital investment through data collection, evaluation, and monitoring, as well as increase the facilitation efforts and cooperation with potential investors and stakeholders.Key Words : Communication Strategy, BPMPD Provinsi Riau, Foreign Investors